Flow-Injection Spectrophotometric System for Sequential Determination of Sugar and Orthophosphate in Soft Drinks and Sugarcane Juice - Kamonthip Sereenonchai; Phanatcha Atsawawiphart; Jiraporn Duangjan; Duangjai Nacapricha; Siriwit Buajarern (Science & Technology Asia, 2022)
This work describes the development of a flow injection (FI) system for sequential analysis of sucrose and orthophosphate in soft drinks and sugarcane juice. A simple sample preparation was firstly employed in order to avoid disturbance from sample matrix such as color of the sample, CO2 gas in soft drink and high turbidity of sugarcane juice. Detection of sucrose was carried out by utilizing the schlieren or lens effect, a well-known phenomenon of light refraction in the visible spectrophotometric FI system. The difference in refractive index at the liquid interfaces between sample plug and water carrier causes light refraction, resulting in a peak signal of sucrose in the sample. Subsequently, the same sample plug was analyzed for the orthophosphate content based on the molybdenum blue method. This FI system only used one visible detector at 880 nm for detecting both the sucrose and orthophosphate signals. Under the optimum condition, linear working range for sucrose and orthophosphate were obtained from 1-50 degree Brix and 5-300 mg P2O5 L-1, respectively, with the determination of coefficient (r2) more than 0.990. The developed system provides rapid analysis, within 3.5 min per sample, of the two analytes. The system was successfully applied to determine sucrose and orthophosphate in soft drinks products and sugarcane juice.